Bridging Analytical Thinking Skills and Artificial Intelligence (AI): A New Path for Solving Mathematical Problems in Elementary Education - Mardin La Ode (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2025)
This study aims to investigate whether there is a relationship between analytical thinking skills and the use of Artificial Intelligence (AI) in solving mathematics problems among students of SD Inpres 14, Sorong Regency. The research employed a quantitative correlational approach with a saturated sample of 26 fifth-grade students. The instruments used included an analytical thinking skills test, classroom observation, and analysis of students’ work documents (answer sheets). Data were analyzed using both descriptive and inferential statistics (Pearson correlation test and independent samples t-test). The main findings revealed a significant negative correlation between analytical thinking scores and AI usage intensity (correlation coefficient r ≈ –0.65, p < 0.01), indicating that students who relied more heavily on AI tended to have lower analytical thinking scores. The t-test comparing two groups (high vs. low AI use) also showed a significant difference in analytical skills (t(24) ≈ –7.21, p < 0.01). These results confirm the research hypothesis that there is a negative relationship between AI usage and students’ analytical thinking abilities. In conclusion, although AI can facilitate mathematical concept comprehension, excessive reliance on it may reduce students’ independent analytical capacity. The findings highlight the importance of teachers’ roles in guiding students to use AI wisely while maintaining active analytical engagement during problem-solving.